2018
DOI: 10.20944/preprints201801.0154.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying Chaos by Various Computational Methods. Part 1: Simple Systems

Abstract: The first part of the paper was aimed at analyzing the given nonlinear problem by different methods of computation of the Lyapunov exponents (Wolf method [1], Rosenstein method [2], Kantz method [3], method based on the modification of a neural network [4, 5], and the synchronization method [6, 7]) for the classical problems governed by difference and differential equations (Hénon map [8], hyper-chaotic Hénon map [9], logistic map [10], Rössler attractor [11], Lorenz attractor [1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Note that the maximal Lyapunov exponents computed directly from time series X 1 and X 2 are underestimated if compared to the maximal exponents for the coupled systems in (26). This effect is well known for synchronized differential equations [38]. Nevertheless, both methods demonstrate that the coupled systems become less chaotic when the coupling parameter is increased.…”
Section: Synchronization Measure Based On a Geometricmentioning
confidence: 92%
“…Note that the maximal Lyapunov exponents computed directly from time series X 1 and X 2 are underestimated if compared to the maximal exponents for the coupled systems in (26). This effect is well known for synchronized differential equations [38]. Nevertheless, both methods demonstrate that the coupled systems become less chaotic when the coupling parameter is increased.…”
Section: Synchronization Measure Based On a Geometricmentioning
confidence: 92%
“…e values of the highest Lyapunov exponent calculated by the Rosenstein method, the Wolf method, and the Sano-Sawada method for classical problems are in good agreement with each other. Along with the indicated methods for calculating Lyapunov exponents, there is the Kantz method [9] and the modified neural network method [36]. It is worth noting that the calculation of the Lyapunov exponent spectrum using the modification of neural networks takes a longer time compared to the Sano-Sawada method.…”
Section: Hénon Mapmentioning
confidence: 99%
“…In recent years several numerical strategies have been suggested for estimating LEs in case of non-smooth dynamic systems. A thorough review can be found in [20]. Recently an approximate numerical method based on the estimation of the Jacobian matrix by perturbation method of the initial orthogonal vectors involving an Euler forward scheme has been proposed [14].…”
Section: Introductionmentioning
confidence: 99%